Short to medium term outcomes of right ventricular outflow tract stenting as initial palliation for symptomatic infants with complete atrioventricular septal defect with associated tetralogy of Fallot. Issue 7 (6th October 2020) - Abumehdi, Mohammad; Al Nasef, Mohamed; Mehta, Chetan; Botha, Phil; McMahon, Colin; Oslizlok, Paul; Walsh, Kevin P.; McCrossan, Brian; Kenny, Damien; Stümper, Oliver
Abstract: Objectives: To assess the impact of right ventricular outflow tract (RVOT) stenting as the primary palliation in infants with complete atrioventricular septal defect with associated tetralogy of Fallot (cAVSD/TOF). Background: Historically, palliation of symptomatic patients with cAVSD/TOF has been achieved through surgical systemic to pulmonary artery shunting. More recently RVOT stenting has evolved as an acceptable alternative in patients with tetralogy of Fallot. Methods: Retrospective review of all patients with cAVSD/TOF who underwent RVOT stenting as palliation over a 13‐year period from two large tertiary referral centers. Results: Twenty‐six patients underwent RVOT stenting at a median age of 57 days (interquartile range [IQR] 25.5–106.5). Median weight for stent deployment was 3.7 kg (IQR 2.91–5.5 kg). RVOT stenting improved oxygen saturations from a median of 72% (IQR 70–76%) to 90% (IQR 84–92%), p  < .001. There was a significant increase in the median Z‐score for both branch pulmonary arteries at median follow‐up of 255 days (IQR 60–455). Eight patients required RVOT stent balloon dilatations and 8 patients required re‐stenting for progressive desaturation. The median duration between reinterventions was 122 days (IQR 53–294 days). Four patients died during the follow‐up period. No deaths resulted from the initial intervention. To date, definitive surgical intervention was achieved in 19 patients (biventricular repair n = 15) at a median age of 369 days (IQR 223–546 days). Conclusion: RVOT stenting in cAVSD/TOF is a safe and effective palliative procedure in symptomatic infants, promoting pulmonary artery growth and improving oxygen saturations.